Recovery of Proteins and Structural and Functional Properties of Corn Starch Processing Wastewater by Foam Separation Coupled with Ultrafiltration - Rui ZHANG; Haitian LI; Zhiwei GAO; Danyi LIU; Jianchun HAN; Longwei JIANG (Shipin gongye ke-ji)
In order to solve the problem of difficult recovery of protein in corn starch processing wastewater and realize the resource utilization of wastewater. In this study, the foam separation coupled with ultrafiltration (UF) method was proposed to recover the protein therein, and the effect of different parameter conditions on protein retention were investigated. The optimal process parameters were determined by single-factor and response surface design methods, and then alcohol precipitation (AP), ammonium sulfate precipitation (ASP), and microporous resin (MPRS) methods were then adopted to extract the protein, respectively. The protein structures were characterized by scanning electron microscopy, Fourier transform infrared spectroscopy (FTIR), ultraviolet spectroscopy, and intrinsic fluorescence spectroscopy. The properties of proteins extracted by three methods were analyzed by solubility, water-holding capacity, oil-absorbent property, foaming and foam stability, emulsifying and lactation stability. The optimal process parameters were determined when the pH of the wastewater was 8, the flow rate was 100 L/h, and the temperature was 40 ℃, at which the protein retention rate could reach up to 92.93%. AP protein was in the form of milky dispersed granules with poor stability. ASP protein was in the form of milky continuous fluffy with good water holding, oil absorption, and foam stability. MPRS protein was slightly yellowish, dense and smooth, and had better solubility, foam stability, emulsification and emulsion stability than the other two proteins. When the pH was 10, the emulsifiability and emulsion stability of MPRS protein reached the maximum of 5.62 m2/g and 12.92 min, respectively, indicating that the protein extracted by the macroporous resin method had a greater potential for application in the food industry.